2017
DOI: 10.1590/s1679-45082017rc4008
|View full text |Cite
|
Sign up to set email alerts
|

Yolk sac primary tumor of mediastino: a rare case in a young adult

Abstract: Germ cell tumors are rare neoplasms that mostly occur in the gonads, although they can also affect other body sites, especially the anterior mediastinum (50 to 70% of all extragonadal germ cell tumors). We report a case of a primary mediastinal yolk sac tumor, a rare and aggressive germ cell tumors subtype. This was a 38-year-old man who was admitted to Hospital do Servidor Público Estadual “Francisco Morato de Oliveira”, complaining about dyspnea and dry cough for 1 year. The computed tomography scan of his c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Meanwhile, the VIP regimen, as another alternative of chemotherapy, was reported to have the similar efficacy to BEP, and it is more suitable for patients who are awaiting surgery because of the lower pulmonary toxicity. However, similar to the case in our report, some studies have showed that BEP and VIP have no significant effect on tumor size 6,15,19,20 . To date, opinions on the necessity of chemotherapy and the selection of chemotherapy scheme, still remains controversial.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Meanwhile, the VIP regimen, as another alternative of chemotherapy, was reported to have the similar efficacy to BEP, and it is more suitable for patients who are awaiting surgery because of the lower pulmonary toxicity. However, similar to the case in our report, some studies have showed that BEP and VIP have no significant effect on tumor size 6,15,19,20 . To date, opinions on the necessity of chemotherapy and the selection of chemotherapy scheme, still remains controversial.…”
Section: Discussionsupporting
confidence: 84%
“…In PubMed, the English case reports and case series of PMYST during the past decade were searched. The following key words were used for the database search: “yolk sac tumor,” “mediastinum,” “mediastinal.” A total of 73 articles were retrieved, in which 22 articles on the therapy and prognosis of PMYST were extracted, including 16 case reports and 6 case series, involving 52 patients in total 5–26 . Out of all the patients, only six female cases were reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They often occur in the middle axis of the body, such as the brain, mediastinum, and retroperitoneum. 1 Mediastinal YSTs are more popular in infancy and post-puberty. 2…”
Section: Introductionmentioning
confidence: 99%
“…Patients often present with advanced, bulky tumors that are unresectable. A comprehensive treatment with initial chemotherapy followed by surgical removal of all residual tumors is recommended 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive treatment with initial chemotherapy followed by surgical removal of all residual tumors is recommended. [3][4][5][6]…”
Section: Introductionmentioning
confidence: 99%